(Ù†Ù‚Ù„ ÙˆØªØ®Ø±ÙŠØ¬ Ù…Ø³Ø£Ù„Ø© Ù…Ø§ ÙŠØªØ¨Ø¹ Ø§Ù„Ø£Ø±Ø¶ ÙÙŠ Ø§Ù„Ø¨ÙŠØ¹ Ø¹Ù„Ù‰ Ù…Ø³Ø£Ù„Ø© Ù…Ø§ ÙŠØªØ¨Ø¹Ù‡Ø§ ÙÙŠ Ø§Ù„Ø±Ù‡Ù† Ø¹Ù†Ø¯ Ø§Ù„Ø´Ø§ÙØ¹ÙŠÙ‘Ø© (Ø¯Ø±Ø§Ø³Ø© ÙÙ‚Ù‡ÙŠÙ‘Ø© - Imam Riadi (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2019)
The study aimed at 1) determining the meaning of naql and takhrij in madzhab syafi'i through the example case of naql and takhrij regarding land transaction on which are trees and buildings, if the trees and buildings are not excluded in the contract, are they automatically sold with the land with the problem of land used as collateral for debt, if on the land are trees and buildings, do they automatically become parts of the collateral, 2) explaining each of the problems and khilaf of syafi'i scholars in it as well as the opinions of other Islamic scholars of different mazhab fiqh, 3) explaining the naql and takhrij method in both of these problems and explaining their strong and weak sides. This research employed deductive-inductive method. The result shows that 1) Naql and takhrij are analogizing the two problems mentioned by the imam mazhab with different laws, then they who make takhrij see that the two problems have no significant difference so that they analogize their laws with each other, then the result is that each problem has two laws: the law mentioned by the imam mazhab and the law resulting from the takhrij method, 2) equalizing the problem of land transaction on which are trees and buildings, if the trees and buildings are not excluded in the contract with the problem of land used as collateral for debt if on the land are trees and buildings are they automatically included in the contract is a weak analogy because there is a significant difference between the two that causes the law of the both unable to be equated in in this matter.